Hubungan Peran Sosial terhadap Tingkat Depresi pada Lansia: The Relationship of Social Roles to the Level of Depression in the Elderly - Prischa Amelliana Dewi; Suci Tuty Putri; Imam Tri Sutrisno (Fakultas Keperawatan Universitas Andalas, 2024)
Depression in the elderly is a serious problem that significantly affects their quality of life. The causes of depression are based on social factors, namely social isolation, loss of a life partner, decreased social support, and changes in social roles. The aim of this research is to determine the relationship between social roles and levels of depression in the elderly. This research uses quantitative descriptive with a cross-sectional approach. The sample in this study was 100 elderly people aged 60-69 years at the UPTD Ledeng Health Center, Bandung City. This study was conducted for 3 weeks in April 2024. The sampling technique uses purposive sampling. This research instrument used a social role questionnaire and the Geritatric Depression Scale (GDS15) questionnaire. Data analysis used bivariate analysis and Pearson correlation test.Most of the 54 respondents (54%) were in the poor social role category. Most respondents experienced mild depression, 58 people (58%). Further analysis of the Pearson correlation test obtained a significance value of 0.009 α (<0.05). This research shows that there is a relationship between social roles and levels of depression in the elderly. Based on the results of this study, the elderly can increase their social role and prevent depression levels by providing social support so that the elderly are involved in social activities with light responsibilities and implementing social intervention programs that focus on increasing their social involvement. These programs can include group activities, elderly communities, or community events specifically designed to strengthen social networks and support mental well-being.